2022
DOI: 10.1021/acs.molpharmaceut.2c00553
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of the Zinc Oxide Nanoparticles Coated with Low-Molecular-Weight Heparin and Doxorubicin Complex In Vitro and In Vivo

Abstract: Various metal oxide nanomaterials have been widely used as carriers to prepare pH-sensitive nanomedicines to respond to the acidic tumor microenvironment promoting antitumor efficiency. Herein, we used zinc oxide nanoparticles (ZnO NPs) as metal oxide nanomaterial coated with low-molecular-weight heparin (LMHP) and doxorubicin (DOX) complex (LMHP-DOX) to prepare ZnO-LD NPs for controllable pH-triggered DOX release on the targeted site. Our results indicated that the released DOX from ZnO-LD NPs was pH-sensitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 65 publications
(92 reference statements)
1
7
0
Order By: Relevance
“…In cancerous 4T1, there was little to no role of caveolae-mediated endocytosis in the uptake of either the bare (FH) or peptide-modified (TFH) nanoparticles, which was consistent with the basal caveolin-1 expression levels in those cells. Both the bare (FH) and peptide-modified (TFH) nanoparticles seemed to be following a combination of clathrin- and lipid-raft-dependent endocytosis to be taken up by the cells, consistent with other reports of how nanoparticles are endocytosed in 4T1 . Mucin-1, a transmembrane mucin and known to be involved in cancer progression like Mucin-16, has been shown to predominantly follow the clathrin-mediated route for cellular entry …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In cancerous 4T1, there was little to no role of caveolae-mediated endocytosis in the uptake of either the bare (FH) or peptide-modified (TFH) nanoparticles, which was consistent with the basal caveolin-1 expression levels in those cells. Both the bare (FH) and peptide-modified (TFH) nanoparticles seemed to be following a combination of clathrin- and lipid-raft-dependent endocytosis to be taken up by the cells, consistent with other reports of how nanoparticles are endocytosed in 4T1 . Mucin-1, a transmembrane mucin and known to be involved in cancer progression like Mucin-16, has been shown to predominantly follow the clathrin-mediated route for cellular entry …”
Section: Discussionsupporting
confidence: 88%
“…Both the bare (FH) and peptide-modified (TFH) nanoparticles seemed to be following a combination of clathrin-and lipid-raft-dependent endocytosis to be taken up by the cells, consistent with other reports of how nanoparticles are endocytosed in 4T1. 54 Mucin-1, a transmembrane mucin and known to be involved in cancer progression like Mucin-16, has been shown to predominantly follow the clathrin-mediated route for cellular entry. 55 Upon internalization, caveosomes, small grape-like multicaveolar structures, appear in the cytoplasm, which may be independent moieties never fusing with lysosomes.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The findings revealed that ZnO LD NPs significantly increased intracellular ROS levels and the expression of caspase 3/7, leading to apoptosis of tumor cells. Thus, ZnO LD NPs can be considered as effective pH‐sensitive nanocarrier systems for tumor treatment and imaging 48 …”
Section: Nano Platform Of Zno Nmts For Cancer Treatmentmentioning
confidence: 99%
“…Thus, ZnO LD NPs can be considered as effective pH-sensitive nanocarrier systems for tumor treatment and imaging. 48 ZnO NMts exhibit pH-dependent dissolution, particularly at low pH, leading to the release of Zn2+ ions. This dissolution process triggers the production of ROS in cancer cells, resulting in specific toxicity towards these cells.…”
Section: Cancer Treatmentmentioning
confidence: 99%
“…Results show that, in comparison to anticancer drugs alone, the compounds ZnO and doxorubicin have strong therapeutic e cacy to inhibit the growth of lung cancer cells. Li et al [11] used zinc oxide nanoparticles coated with heparin and doxorubicin for controllable pH-triggered anticancer release on the targeted site. In-vitro and in-vivo results showed the effectiveness of the compound through endocytosis and ROS on tumor cells (PC-3M and 4T1).…”
Section: Introductionmentioning
confidence: 99%